The Analysis of The Implementation of Industry-Academia Programme For Diploma In Civil Engineering Students at Politeknik Sultan Haji Ahmad Shah Towards Developing Holistic Graduates - Mohamed, Siti Asmahani; Zainal, Rozallienny (Proceeding Economy of Asia International Conference, 2026)
Introduction/Main Objectives: This study aims to examine the effectiveness of the Industrial Visiting Lecturer Programme (PPI) for the Diploma in Civil Engineering (DKA) at Politeknik Sultan Haji Ahmad Shah (POLISAS) in producing holistic graduates. Background Problems: The study was conducted based on the PPI activities for the June 2022 Session involving the Diploma in Civil Engineering Programme. A total of 446 DKA students participated in the PPI programme and were selected as respondents. Five main programmes were implemented for semester two(2) until semester five (5). Research Methods: The research employed a quantitative descriptive design. The instrument used was a questionnaire based on a Likert scale ranging from 1 to 5, representing poor to excellent. The questionnaire was developed by the Department of Polytechnic and Community College Education (JPPKK) and the data was analyzed using Statistical Package for the Social Sciences (SPSS) version 19.0. The analysis involved median and standard deviation values. The validity and reliability of the instrument were assessed using Cronbach Alpha. Finding/Results: Data were analysed using mean and standard deviation. The findings indicate that all items recorded median values between 4.1 and 4.4, reflecting a high level of satisfaction. The standard deviation value was low (0.7), indicating consistency in the respondents’ responses. The Cronbach Alpha value was 0.910, indicating high reliability of the instrument. Conclusion: In conclusion, the study proves that industrial exposure directly contributes to students’ academic development, character building, and employability — which are dominant attributes in producing holistic graduates